2019
DOI: 10.1039/c9nr03332g
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer excitons in bilayer MoS2 under uniaxial tensile strain

Abstract: Evidence of the interlayer exciton transition at the K point in bilayer MoS2 through tensile strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 21 publications
2
49
0
Order By: Relevance
“…Previous studies [27,28,29] indicated that the spectrum of bare MoS 2 should display two distinctive peaks: A 1s exciton peak between 1.86 and 1.92 eV and B 1s exciton peak within the range of 2.0-2.1 eV, which are associated with direct optical transitions to the lowest conduction bands from the highest spin-orbit valence bands [30,31,32]. It should be noted that both A 1s and B 1s exciton peaks are formed by an electron and a hole in the valence band.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies [27,28,29] indicated that the spectrum of bare MoS 2 should display two distinctive peaks: A 1s exciton peak between 1.86 and 1.92 eV and B 1s exciton peak within the range of 2.0-2.1 eV, which are associated with direct optical transitions to the lowest conduction bands from the highest spin-orbit valence bands [30,31,32]. It should be noted that both A 1s and B 1s exciton peaks are formed by an electron and a hole in the valence band.…”
Section: Resultsmentioning
confidence: 98%
“…The strain tunable interlayer distance could explain the large gauge factor observed for bilayer MoS 2 upon biaxial strain as Deilmann and Thygesen demonstrated through density functional theory calculations that the interlayer exciton position strongly depends on the interlayer distance [24]. In previous uniaxial strain works, on the other hand, because of the Poisson's ratio of the polycarbonate substrate (ν=0.37) when the flake is uniaxially stretched in one direction it is compressed in the perpendicular direction (within the basal plane) [37] counteracting most of the Poisson's effect induced upon uniaxial tension [16].…”
mentioning
confidence: 98%
“…Moreover, heterostructures built with these 2D systems have also attracted the interest of the scientific community because of the presence of interlayer excitons: excitons formed by electrons and holes that live in different layers [9][10][11][12][13]. Very recently, Gerber et al and Slobodeniuk et al demonstrated that naturally stacked bilayer MoS 2 (2Hpolytype) also presents interlayer excitons, with high binding energy, that can be observed at room temperature [14,15] and Niehues et al demonstrated that uniaxial strain could be used to tune the energy of the interlayer exciton [16].…”
mentioning
confidence: 99%
“…[9][10][11][12][13] Very recently, Gerber et al and Slobodeniuk et al demonstrated that naturally stacked bilayer MoS2 (2H-polytype) also presents interlayers excitons, with high binding energy, that can be observed at room temperature 14,15 and Niehues et al demonstrated that uniaxial strain could be used to tune the energy of the interlayer exciton. 16 In this work we employ biaxial strain to modify the band structure, and thus the excitonic resonances, in bilayer MoS2 flakes. We observe that both the A and B excitons, as well as the interlayer exciton, substantially redshift upon biaxial tension.…”
mentioning
confidence: 99%